THE DIFFERENCES IN BMI VALUES BETWEEN TOP FOOTBALL AND VOLLEYBALL PLAYERS - Tatjana Popović-Ilić; Biljana Vitošević; Igor Ilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The athletes are, as well as the other population groups, exposed to danger of being overweight. Therefore, it is necessary to constantly control their body composition. The goal of this research is to determine the differences in BMI values between measured groups of football and volleyball players, so we could determine if the specifics of the training process of the observed sports have some influence on the BMI values. The population studied consisted of 100 male athletes of the top national competition rank (57 football players and 43 volleyball players), age 18 - 30. The variables measured are body height and body weight. The BMI of both groups was calculated based on these measures and compared with T-test (sig≥95%). The values produced by T test (sig=83,8%) indicate that there isn't a significant statistical difference between these groups. We concluded that despite the differences in selection and training processes, the practice of professional top sport provides that body composition values are kept in the boundaries of normal values.